PENGARUH PENERAPAN APLIKASI e-FILING TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI KARYAWAN YANG DI MODERASI OLEH DUKUNGAN ORGANISASI DI KAWASAN INDUSTRI EJIP CIKARANG - Muhamad Dedi Kusnadi (FEB Universitas Sultan Ageng Tirtayasa, 2017)
This research is conducted to see the effect of e-filing application on tax payer compliance who are moderated by organization support in EJIP Industrial Park Cikarang, this research is based on the low level of e-Filing usage where the level of achievement of e-Filing reporting in 2016 when compared to the registered taxpayer only 25.76%, whereas the structure of registered taxpayers is dominated by employee individual tax payers. This research focuses on the employee population in EJIP Industrial Park Cikarang with total employees + - 20.000 people with slovin sampling technique obtained sample of 100 samples, testing using SPSS software. The results showed that organizational support has been shown to strengthen the effect of e-Filing on the compliance of employee individual taxpayers.